Fat free mass in patients with ischemic heart disease treated with corrective surgery without heart-lung machine - Raúl Ramón Rizo Rodríguez; Marcia Mesa Díaz; Ana Ibis Núñez Bourón; Ana Beatriz Pupo Leyte Vidal; Yergenia Matute Gaínza (Centro Provincial de Información de Ciencias Médicas, 2016)
A prospective and longitudinal study of 42 adults, of both sexes, with ischemic heart disease, treated with corrective surgery without heart-lung machine was carried out in the Territorial Center of Cardiovascular Surgery in Santiago de Cuba, aimed at measuring the fat free mass by means of the method of electric bioimpedancy, during the first quarter of 2014.  The results showed that the fat free mass average of the postoperative period was significantly higher (p<0,05) than that of the measuring in the preoperative period.  It was concluded that this increase was interpreted presumably as an overestimation caused by organic factors that affected the measuring technique.